2019
DOI: 10.1111/jspn.12267
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting cigarette smoking among adolescents in South Korea, Vietnam, and Thailand

Abstract: Purpose The current study was designed to describe risk and preventive factors related to cigarette smoking among adolescents in South Korea, Vietnam, and Thailand. Design and Methods A cross‐sectional descriptive design was used. Student data were extracted from three national data sets, specifically the Global Youth Tobacco Survey from each country. Complex sampling multinomial logistic regression was performed to find factors related to current smoking. Results The prevalence of cigarette smoking was 4.7% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(81 reference statements)
1
5
2
Order By: Relevance
“…Male were more likely to smoke than female. This result is consistent with previous studies in Thailand [7], [8]. In Thai society, males' smoking is more considered as socially acceptable than smoking by females [9].…”
Section: Discussionsupporting
confidence: 93%
“…Male were more likely to smoke than female. This result is consistent with previous studies in Thailand [7], [8]. In Thai society, males' smoking is more considered as socially acceptable than smoking by females [9].…”
Section: Discussionsupporting
confidence: 93%
“…One positive finding in our results was that only a very small proportion of the adolescents reported tobacco smoking, with 1% reporting having smoked in the past 30 days This rate is lower than reported in some previous studies in Vietnam, with some other studies reporting 9% to 18% of youth experimenting with smoking and 3% to 5% being current smokers (Joung & Chung, 2019 ; Page, Thanh Huong, Chi, & Truong Quang, 2010 ). There are several possible explanations for this difference.…”
Section: Discussioncontrasting
confidence: 62%
“…Moreover, men living in northern Thailand had a statistically greater risk of current smoking than women [38]. A triple country study in 2019 reported that male sex was a strong factor associated with current smoking in the Thai population [39]. A study in the United States in 2017 reported that the use of some substances, such as amphetamines, led to cigarette use [40].…”
Section: Discussionmentioning
confidence: 99%